Pengaruh Solvability dan Firm Size Terhadap Audit Delay Perusahaan Multinasional - Elok Faiqoh Himmah (LPPM UNIBI, 2021)
This study analyzes the effect of solvency and firm size to find out how much influence it has on the Audit Delay of multinational companies in Indonesia. Multinational companies are companies that have a major contribution to gross domestic product which is an essential sector in economic activity in Indonesia. The phenomenon that has occurred in recent years is that in the Indonesian Capital Market, companies are late in reporting financial statements and audit reports. The research method used is quantitative research using multiple linear regression analysis. This study uses secondary data in the form of financial statements and audit reports of public companies listed on the Indonesia Stock Exchange. The sample of this research is 48 companies in two years. This research uses classical assumption test with SPSS tool. The results showed that partially solvability and firm size and had effect on audit delays.